E-Word Of Mouth For Tourism Futures: A Case in Travel Agency - Dinarsiah Chendraningrum (Journal of Tourism Sustainability, 2021)
The development of technology, especially digital media, has encouraged one of the tourism business industries, namely Jacktour, to use the Tripadvisor website to introduce and sell tour packages. Online reviews on websites are crucial to form an e-word mouth that is easy to access by future tourists. This study aims to determine both positive and negative tourist reviews regarding tour packages purchased from Jack Tour. The attributes of the tour packages include tourist attractions, people in charge (PIC), accessibility, transportation, accommodation, restaurants, prices, and final impressions. A qualitative descriptive method was applied to this research; data was collected from Jacktour on the Tripadvisor website. The sampling technique used purposive sampling. From 431 tourist populations, 325 tourists became the sample. From the results of the research, PIC (Person in Charge) is very important and is often reviewed positively or negatively. At the same time, in the impression aspect, tourists are satisfied with the services provided by Jacktour and will recommend it to others.